Analysis of bankruptcy prediction with Altman Z-Score method in Shariah rural bank in Central Java period 2011-2016 - Umi Kholifah; Atieq Amjadallah Alfie; Rosida Dwi Ayuningtyas (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This research describes the implementation of Altman Z-Score to predict sharia rural bank bankruptcy in Central Java since 2011 – 2016. The research background is sharia rural bank competition to achieve public trust, especially small industries as the main funding focus. Qualitative methods is used to this research and analyze annual report of twelve sharia rural bank in Central Java. The annual report were analyzed with Altman Z-Score Modification formula then analyze WCTA, RETA, EBITTA, BVEBVD ratios. Data gained to analyze and scoring sharia rural bank bankruptcy. Based on research analysis shows that Rural Sharia Banking Bankruptcy is raise year by year. In the 2011 to 2016, Rural Sharia Banking in the bankruptcy area are 5, 7, 8, 7, 6, and 9. Although Rural Sharia Banking from 2011 to 2016 which in the grey area are 4, 5, 4, 5, 6, and 3. In the 2011 just 3 Rural Sharia Banking which notice that in the non-bankruptcy level. Based on this research, the manager should to stabilized and to health the bank. It was to banking function runs normally and not going to bankruptcy.